Sustaining One’s Own Health and Wellness While Supporting a Stroke Survivor: Spouses’ and Partners’ Perspectives - Moloczij, Natasha (Auckland University of Technology, 2009)
Utilising an interpretive descriptive approach, this qualitative study explores and identifies how spouses and partners of stroke survivors sustain their own health and wellness. Recent literature has mainly focused on identifying psychological coping strategies thought to assist in adapting to the caring role. As a consequence, there is limited knowledge regarding the experiences of how spouses and partners attend to their own health and well-being. This study aimed to explore how spouses and partners sustain their own health and wellness while supporting a stroke survivor. Purposive and theoretical sampling strategies were used to guide recruitment. Semi-structured interviews were carried out with seven spouses and partners who were living with, and supporting a stroke survivor. A central theme with three sub-themes became apparent when examining spouses and partners’ experiences. The theme of Meeting Needs connects the three sub-themes, in that spouses’ and partners’ health and wellness appeared to be influenced by and intertwined with attending to the stroke survivors’ needs. The context of Being in a Relationship provided a rationale for prioritising the stroke survivors’ needs and was the first sub-theme. Secondly, Living Both Lives explains how spouses/partners were busy thinking and attending primarily to the stroke survivor’s daily requirements whilst also trying to attend their own needs. The third sub-theme, Uncertain Health encompasses how a spouse’s and partner’s well-being is connected to the stroke survivors’ health and their future concerns about being able to provide care if they themselves become sick. Therefore, these circumstances shaped their ability to attend to their own health and well-being. Whilst attending to the stroke survivor was at the forefront of their minds there were some strategies which spouses/partners utilised to support their own health and well-being. These were: creating time and space for themselves; talking with others; and comparing own lives against others who were seen to be worse or better off, in order to support their own emotional well-being. This study found that the participants struggled to prioritise and attend to their own health and well-being, as most of them was busy primarily attending to the stroke survivor’s needs. Overall, results suggest that exploring what spouses/partners think and do within the relationship could be valuable for health practitioners. Given that it is the intimate nature of being in a relationship that is the foundation for spouses/partners supporting the stroke survivor, it could also be important for services and health professionals to consider the well-being and needs of the couple, not just the stroke survivor.
Keywords: Caring for sick; Informal caring; Qualitative; Health; Coping strategies; Support for caregivers